Closed Spontaneous Rupture of the Flexor Tendon in Zone 3: A Case Series - Thitiworakarn, MD, Navapong; Vinitpairot, MD, Chaiyos; Jianmongkol, MD, Surut (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: The pathophysiology of spontaneous rupture is not fully understood. Spontaneous rupture has been questioned, as some authors have stated that most spontaneous ruptures cannot be attributed to a cause or have not yet been investigated. Zone 3 was the most common place for flexor tendon ruptures to happen on their own, but the risk factor was not found. Methods: From 2019 to 2022, we recorded four cases of closed rupture of the flexor tendon in zone 3 caused by agricultural activity. The history of all patients such as steroid injections, pain, and underlying conditions, was reviewed. Some parts of the tendon, debrided from the injury site, were sent for pathologic examination. The final range of motion and activity were recorded. Results: All our patients had acute symptoms while gripping tools and excavating dirt during gardening. All flexor tendon ruptures occurred in zone 3, and were repaired by core and epitendinous suture. There was no actual condition believed to be the cause of the rupture. All patients achieved nearly full range of motion in the final follow-up. Conclusions: A firm grip while performing agricultural tasks appears to be a risk factor of closed rupture flexor tendon. Although it is uncommon for a closed rupture of a flexor tendon injury to occur without ascertainable causes, this condition should be recognized while facing weakness or an inability to flex the finger.